Autopsy Findings in Paediatric Poisoning with Otapiapia - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Otapiapia is a locally prepared insecticide composed of varying strengths of an organophosphate and kerosene. It has been occasionally associated with accidental poisoning. However, there is paucity of data on autopsy findings in pediatric deaths related to organophosphate poisoning, including otapiapia. This report of autopsy findings aims to provide valuable information in these cases and suggest ways to better manage them when they present clinically.Materials and Methods:This is a review of autopsy findings of pediatric cases of accidental poisoning with otapiapia between 2008 and 2016 in a tertiary institution in northwestern Nigeria.Results:Seven cases of otapiapia-related deaths were autopsied during the period reviewed, 4 of which were accidental while infanticide was suspected in the remaining 3. The most common autopsy findings were diffuse alveolar damage followed by cerebral edema and acute tubular necrosis in the kidneys.Conclusion:In cases of otapiapia poisoning that survive to reach medical attention, priority attention should be given to airway and fluid management.